1981
DOI: 10.1128/iai.31.2.547-553.1981
|View full text |Cite
|
Sign up to set email alerts
|

Energy-independent uptake of iron from citrate by isolated outer membranes of Neisseria meningitidis

Abstract: Cyanide-poisoned Neisseria meningitidis SD1C cells rapidly took up 'Fe from iron-citrate complexes during the first 2 min, after which no further iron was accumulated. ['4C]citrate was not taken up concomitantly with 'Fe by these cells.The 'Fe taken up by the poisoned cells was found in the membrane fraction after cells were broken; 70% of the radioactivity was distributed in the outer membrane, and 30% was in the inner membrane. Isolated outer membranes from iron-starved cells were as capable of iron uptake f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…The present studies indicate that highmolecular-weight outer membrane proteins induced during iron limitation may not be in-volved with the initial binding of iron to P. aeruginosa. Similar results were reported by Simonson et al (22) regarding iron uptake by outer membranes of Neisseria meningitidis. Although outer membrane proteins with molecular weights of 84,500 and 69,000 were induced in iron-starved cells, iron citrate complexes bound to a protein with a molecular weight of 36,500.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The present studies indicate that highmolecular-weight outer membrane proteins induced during iron limitation may not be in-volved with the initial binding of iron to P. aeruginosa. Similar results were reported by Simonson et al (22) regarding iron uptake by outer membranes of Neisseria meningitidis. Although outer membrane proteins with molecular weights of 84,500 and 69,000 were induced in iron-starved cells, iron citrate complexes bound to a protein with a molecular weight of 36,500.…”
Section: Resultssupporting
confidence: 90%
“…Outer membrane proteins have been shown to be involved in iron uptake by a variety of organisms (1,10,12,20,22). Iron starvation leads to the induction of several high-molecularweight proteins in the outer membranes of several Pseudomonas spp., including P. aeruginosa (17).…”
mentioning
confidence: 99%
“…With regard to the latter, a previous report by Simonson et al . (10) analyzed the energy-independent binding of "Fe-citrate to membranes from iron-starved meningococci. Analysis of the membranes after incubation with "Fe-citrate by SDS-PAGE showed that the iron isotope comigrated solely with a protein complex having an apparent molecular weight of 36,500 .…”
Section: Resultsmentioning
confidence: 99%
“…(7) originally described the presence of multiple high-molecularweight gonococcal iron-regulated proteins (70,000-100,000); the number and apparent molecular weights of these proteins varied between isolates examined (7)(8)(9) . Similarly, proteins in the same molecular weight range are expressed by meningococci when grown under iron-limiting conditions (10). The molecular mass of these neisserial proteins are similar to the iron-regulated proteins expressed by other Gram-negative organisms and may serve analogous roles in iron acquisition (7) .…”
mentioning
confidence: 93%
“…Most of the iron in human body fluids is not directly available, but remains bound to several plasma proteins: transferrin, haptoglobin (in the total irofi in the organism is bound to transferrin in body fluids;: with a very high affinity constant, Ka ~ around 1036. Many invasive path-Ogens acquire iron from iron-binding proteins by the productiOn of high affinity iron-binding systems which in the case of N. meningt'tidis involves outer membrane receptors, that must make contact with transferrin for iron uptake tO take place [2]. The Neisserial receptor comprises two outer membrane proteins; transferrin binding protein 1 (TBP1, about 98 kDa in most strains) and transferrin binding protein 2 (TBP2, with variable molecular mass between 60 and 90 kDa) [3,4]; their specific roles in the iron-uptake system re-160 mains to be determined although it is presumed that they act by binding the transferrin molecules to facilitate iron utilization.…”
Section: Introductionmentioning
confidence: 99%